2010
DOI: 10.1084/jem.20092531
|View full text |Cite
|
Sign up to set email alerts
|

Calcineurin regulates innate antifungal immunity in neutrophils

Abstract: Patients taking immunosuppressive drugs, like cyclosporine A (CsA), that inhibit calcineurin are highly susceptible to disseminated fungal infections, although it is unclear how these drugs suppress resistance to these opportunistic pathogens. We show that in a mouse model of disseminated Candida albicans infection, CsA-induced susceptibility to fungal infection maps to the innate immune system. To further define the cell types targeted by CsA, we generated mice with a conditional deletion of calcineurin B (Cn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
146
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 139 publications
(158 citation statements)
references
References 47 publications
11
146
0
Order By: Relevance
“…These studies confirmed the lethality data and indicated that IFN-a/b signaling promotes control of C. albicans growth in the early phases of infection, a time at which host defenses primarily depend on the innate immunity system. Indeed, in the disseminated candidiasis model used here, survival and host defenses are known to depend predominantly on the innate, rather than the adaptative, immunity system [21]. Therefore, collectively, these data suggested that IFN-a/b signaling plays a role in stimulating innate host defenses against C. albicans.…”
Section: Signaling Requirements For Ifn Inductionmentioning
confidence: 58%
“…These studies confirmed the lethality data and indicated that IFN-a/b signaling promotes control of C. albicans growth in the early phases of infection, a time at which host defenses primarily depend on the innate immunity system. Indeed, in the disseminated candidiasis model used here, survival and host defenses are known to depend predominantly on the innate, rather than the adaptative, immunity system [21]. Therefore, collectively, these data suggested that IFN-a/b signaling plays a role in stimulating innate host defenses against C. albicans.…”
Section: Signaling Requirements For Ifn Inductionmentioning
confidence: 58%
“…Thus, induction and activation of NFATc1 by TNF provide a mechanistic explanation by which TNF can induce giant cell formation in infectious granulomas such as in Mycobacterium tuberculosis infection (38) and in TNF-driven chronic granulomatous diseases such as sarcoidosis (39). In addition to fusion and osteoclastogenesis, NFAT regulates cytokine production, including TNF production, in myeloid cells (14,15,35) and thus can play an important role in myeloid cell biology independently of osteoclast differentiation. Context-dependent function of NFAT is determined by its interactions with NF-κB and AP-1 proteins that direct NFAT to composite binding sites present in different target genes (9).…”
Section: Tnf Primes Macrophages For Increased and More Rapid Responsementioning
confidence: 99%
“…The function of NFATs is context dependent and modulated by interactions with other transcription factors, in particular, AP-1 proteins (9, 13). More recently, functions of NFAT in myeloid cells are emerging, including modulation of cytokine production (14,15), DC survival (16), and induction of cell fusion and differentiation into osteoclasts (17). In myeloid cells, basal NFAT expression is low and the strong activation of NFAT necessary for driving cell fusion and osteoclast differentiation requires two signals: induction of NFAT expression via NF-κB and AP-1 and posttranslational activation by Ca 2+ -Cn signaling induced by ITAM-associated immunoreceptors (18,19).…”
mentioning
confidence: 99%
“…Neutrophilic airway inflammation is now well recognized as being a feature of severe asthma (3)(4)(5) and ABPA (6,7). During acute infection, neutrophils are crucial for antifungal defense (8,9), and lack of neutrophils is the best appreciated risk factor for invasive aspergillosis (10). However, uncontrolled neutrophil infiltration in Aspergillus-induced allergic disorders positively correlates with tissue damage and loss of lung function (6,11).…”
Section: Th17 | Tolerancementioning
confidence: 99%